2017
DOI: 10.3390/children4050032
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Mindfulness Meditation for Pediatric Chronic Pain

Abstract: Despite advances in psychological interventions for pediatric chronic pain, there has been little research examining mindfulness meditation for these conditions. This study presents data from a pilot clinical trial of a six-week manualized mindfulness meditation intervention offered to 20 adolescents aged 13–17 years. Measures of pain intensity, functional disability, depression and parent worry about their child’s pain were obtained at baseline and post-treatment. Results indicated no significant changes in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…On multiple occasions, participants went beyond simply describing foundational practices, such as sitting meditation, and were able to share high-level concepts, such as insight that their pain is connected to stress. This specific association has been described in previous in-person MBI studies and considered an indicator of increased mindfulness [16].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…On multiple occasions, participants went beyond simply describing foundational practices, such as sitting meditation, and were able to share high-level concepts, such as insight that their pain is connected to stress. This specific association has been described in previous in-person MBI studies and considered an indicator of increased mindfulness [16].…”
Section: Discussionsupporting
confidence: 74%
“…reported benefiting from meeting others with whom they had a shared lived experience, which is frequently reported in in-person studies of MBIs in pediatric populations [11,16].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Attrition and recruitment problems were described in five of the studies (Hesse, Holmes, Kennedy-Overfelt, Kerr, & Giles, 2015;Jastrowski Mano et al, 2013;Lovas et al, 2017;Ruskin, Gagnon, Kohut, Stinson, & Walker, 2017;Ruskin, Kohut, & Stinson, 2015) as well as problems with obtaining sufficient post test data to draw valid conclusion about outcome (Ruskin, Gagnon, Kohut, Stinson, & Walker, 2017). However, three other recent studies indicate better feasibility results with low attrition and high acceptability but heterogeneous results when it comes to potential efficacy (Ali et al, 2017;Chadi et al, 2016;Waelde et al, 2017). Ali et al (Ali et al, 2017) conducted an open trial on 18 adolescents with various FSS and found preliminary evidence for the MBSR programme with regard to improvement of functional disability, symptom impact and anxiety with consistency between parent and child measures.…”
Section: Evidence For Fss In Children and Adolescentsmentioning
confidence: 99%
“…They reported no improvements in psycho-logical or pain symptoms but did find significant reductions in pre and post-mindfulness session salivary cortisol levels. Waelde et al (Waelde et al, 2017) conducted an open trial on 20 adolescents with chronic pain who received a six-week group intervention based on an adult programme named 'Inner Resources for Stress' combining meditation practices, breath-focused cue word repetition and visualisation. Functional disability and frequency of pain complaints improved with small effect sizes (d = 0.2-0.3).…”
Section: Evidence For Fss In Children and Adolescentsmentioning
confidence: 99%